Influência do antagonismo por bactérias ácido-láticas e da maturação sobre a viabilidade de mycobacterium bovis bcg em queijos tipo minas artesanal. - Leticia Goulart de Oliveira (2018)
The consumption of raw milk and its products is considered one of the main risk factors associated with zoonotic tuberculosis in humans, a disease caused by Mycobacterium bovis. In the state of Minas Gerais, Minas artisanal cheese is the main artisanal dairy product, and is made from raw milk in rural properties in the countryside. Lactic acid bacteria (LAB) are a group of microorganisms derived from milk and its products which present inhibitory activity against pathogens, including mycobacteria. The aim of this study was: (I) to assess in vitro antagonistic activity of LAB isolated from Brazilian Minas artisanal cheese against M. bovis BCG; (II) to isolate and to quantify M. bovis BCG in experimental Minas artesanal cheese during controlled ripening. In the in vitro analysis, nine LAB were tested against M. bovis BCG on five different assays: spot on the lawn; antagonistic activity in 7H9 broth and in fermented milk, and antagonistic activity of LAB supernatants. L. paracasei A1C, L. rhamnosus D1C, L. plantarum 1CV and L. plantarum 56CV demonstrated better antagonistic activity in all assays. This could be due to their own characteristics such as growth rate, acid and bacteriocin production. Mycobacterium bovis BCG viability was also tested in Minas artesanal cheeses during ripening for 90 days. Cheeses were made according to three diferente treatments: control treatment, cheeses with M. bovis BCG and cheeses with L. paracasei, L. rhamnosus and M. bovis BCG. The analysis were performed on days 1, 8, 15, 22, 29, 45, 60 and 90 after the cheeses production. The following parameters were examinated throughout the ripening period: counts of LAB, M. bovis BCG, coliforms at 30ºC and 45ºC, Staphylococcus spp., coagulase-positive Staphylococcus, fungi; presence of Salmonella spp.; pH; concentrations of lactic acid, moisture, total dry matter, deffated dry matter, fat, protein and sodium chloride. The micobacteria was not detected only after 45 days in cheeses with LAB and 60 days in cheeses without LAB. The main factors associated with the absence of the micobacteria were the presence of LAB and the decline of the moisture contente of the cheese.